A bump in the node: The hydraulic implications of rhizomatous growth. Issue 1 (9th January 2023) - Suissa, Jacob S.; Agbleke, Andrews A.; Friedman, William E.
Abstract: Premise: Rhizomatous growth characterizes numerous taxa among vascular plants. While abundant information exists on nutrient sharing and demography, the question of how these metameric organisms move water through their bodies remains largely unstudied. Moreover, we lack an understanding of the evolutionary implications of rhizomatous growth across vascular plants. Here, we examined these questions by investigating how rhizomatous growth and vascular construction affect whole‐plant hydraulic function. Methods: In five terrestrial fern species with diverse vascular construction, we used microcomputed tomography and bright‐field microscopy to examine vascular construction across nodes along the rhizome. These data were integrated with measurements of leaf stomatal conductance under rooted and uprooted conditions to relate vascular patterning and hydraulic architecture to leaf water status. Results: Similar to phytomers of woody seed plants, nodal regions in rhizomatous ferns are areas of hydraulic resistance. While water is shared along the rhizomes of these investigated species, hydraulic conductivity drops at nodes and stomatal conductance declines when nodes were locally uprooted. Together, our data suggest that nodes are chokepoints in axial water movement along the rhizome. Conclusions: Nodal chokepoints decrease hydraulic integration between phytomers. At the same time, chokepoints may act as "safety valves", hydraulically localizing each phytomer—potentially decreasing embolism and pathogen spread. This suggests a potential trade‐off in the principal construction of the fern rhizome. Moreover, we propose that shoot‐borne roots (homorhizy) and the prostrate habit of rhizomatous ferns decrease the hydraulic and structural burdens that upright plants typically incur. The absence of these hydraulic and structural demands may be one reason ferns (and many rhizomatous plants) lack, or have minimally developed, secondary xylem.